A comprehensive set of transcript sequences of the heavy metal hyperaccumulator Noccaea caerulescens - Lin, Ya-Fen; Severing, Edouard I.; te Lintel Hekkert, Bas; Schijlen, Elio; Aarts, Mark G. M. (Frontiers in Plant Science, 2014)
Noccaea caerulescens is an extremophile plant species belonging to the Brassicaceae family. It has adapted to grow on soils containing high, normally toxic, concentrations of metals such as nickel, zinc and cadmium. Next to being extremely tolerant to these metals, it is one of the few species known to hyperaccumulate these metals to extremely high concentrations in their aboveground biomass. In order to provide additional molecular resources for this model metal hyperaccumulator species to study and understand the mechanism of heavy metal exposure adaptation, we aimed to provide a comprehensive database of transcript sequences for N. caerulescens. In this study, 23830 transcript sequences (isotigs) with an average length of 1025 bps were determined for roots, shoots and inflorescences of N. caerulescens accession ‘Ganges’ by Roche GS-FLEX 454 pyrosequencing. These isotigs were grouped into 20,378 isogroups, representing potential genes. This is a large expansion of the existing N. caerulescens transcriptome set consisting of 3705 unigenes. When compared to a Brassicaceae proteome set, 22,232 (93.2%) of the N. caerulescens isotigs (corresponding to 19191 isogroups) had a significant match and could be annotated accordingly. Of the remaining sequences, 98 isotigs resembled non-plant sequences and 1386 had no significant similarity to any sequence in the GenBank database. Among the annotated set there were many isotigs with similarity to metal homeostasis genes or genes for glucosinolate biosynthesis. Only for transcripts similar to Metallothionein3 (MT3), clear evidence for an additional copy was found. This comprehensive set of transcripts is expected to further contribute to the discovery of mechanisms used by N. caerulescens to adapt to heavy metal exposure.